Experimental study on discharge of large cavity inductively coupled plasma - Zhaoyang Zhang; Fan Lei; Xiaolong Wei; Xinmin Han; Hui Zhou (AIP Advances)
Plasma stealth technology has the advantages of a large absorption bandwidth, easy control, and long-term operation. A large-scale plasma discharge experimental device was designed, and the multi physics simulation platform COMSOL was used to simulate the plasma. Typical parameters such as electron density and electron temperature during discharge were analyzed; the radar cross sections- simulation measurement of the inductively coupled plasma model used in this study was performed using CST software; and the plasma stealth function was proved, which provided the basis for the subsequent plasma stealth experiment.